Connected Cars and Smart Roads Using ARM and Wireless Sensor Network - Parthasaradhy, P.; Manjunathachari, K. (International Journal of Engineering and Technology, 2026)
Majority of the road accidents these days are caused due to driver slackness, bad road conditions and bad weather conditions. The ever growing death toll and lack of information to show up such emergences is being a great alarm. We propose a method of resolving the challenge described above by employing smart car communication technique along with a connected vehicle concept. An embedded processer along with a GPS receiver is incorporated into the connected car’s dashboard to read the vehicle co-ordinates. Along with the GPS co-ordinates, the smart car also identifies for other objects in the road in its proximity and the movement of the car are controlled based the proximity sensors input. When a fatal accident happens in such case, an emergency alert using mobile message is sent to the nearest help line center along with the cars GPS co-ordinates.